Exploration of the Shared Genes and Molecular Pathways between Pre-Eclampsia and Type 2 Diabetes Mellitus via Co-Expression Networks Analysis - Zhifang Ding; Lingling Cao; Rui Jin; Rui Li (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: Pre-eclampsia is a serious disorder associated with pregnancy, but its etiology remains poorly understood. In this study, we aimed to explore the shared genes and molecular pathways between pre-eclampsia and type 2 diabetes mellitus (T2DM). Methods: The record of 2160 pregnant women who had pre-eclampsia risk assessed by placental growth factor (PIGF) levels in Fuyang People’s Hospital, China were retrospectively reviewed. The microarray datasets of pre-eclampsia and T2DM were searched in the Gene Expression Omnibus (GEO) and were downloaded for secondary analysis. Results: According to the PIGF stratification, the high-risk group had a significantly higher proportion of T2DM than the low-risk group (51/326, 15.6% vs. 1.4%, p < 0.001). An overlapping geneset containing 30 members between pre-eclampsia and T2DM was identified. The significantly enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were “Rap1 signaling pathway”, “Aldosterone synthesis and secretion”, “Phosphatidylinositol signaling system”, “Neurotrophin signaling pathway”, “Aldosterone-regulated sodium reabsorption” and “Insulin signaling pathway”. Combined with previous research findings, we infer that impaired PI3K/Akt signaling pathway may be a common pathogenetic factor of T2DM and pre-eclampsia. The gene ontology (GO) analysis confirmed that the shared genes were enriched in several Biological Process (BP) terms directly related to insulin-PI3K-Akt signaling pathways. Conclusions: Impaired PI3K/Akt signaling pathway might be a common pathogenetic factor of T2DM and pre-eclampsia. For activating purposes, self-management behaviors, including self-monitoring of blood glucose, healthy diet, physical activity and medication adherence should be highly recommended during nursing practice for pregnant women with pre-existing T2DM.